A Review Paper on Fuzzy Logic Algorithms (International Journal of Innovative Research in Computer Science & Technology, 2021)
Logic for gene expression analysis in a  flurry. We developed a new method for analyzing gene  expression data. To convert expression values into  Quality descriptors, this method uses a fluid logic that can  be evaluated using heuristic rules. We developed a model  for identifying three different activators, repressors, and  objectives in a data set for yeast gene expression in our  experiments. The test predictions generated by an  algorithm match the experimental data in the literature  very well. Algorithms can identify a much larger number  of transcription factors that could be identified at random  in defining the function of unspecified proteins. Using  only expression data in the form of clustering, this  method allows the user to construct a linked network of  genes. The interpretation of gene expression  categorization models is typically difficult, however, it is  an essential component of the analysis procedure. In five  databases ranging in size, experimental origin, and  physiological field, we investigate the effectiveness of  micro rules fuzzy systems. The classifiers resulted in  regulations that are simple to understand for biomedical  researchers. The classifiers resulted in regulations that are  simple to understand for biomedical researchers.
Keywords: Algorithm; Data; Fuzzy logic; Gene; Models